‘Systems approach’ plant breeding illustrated by trees - Graudal, Lars; Dawson, Ian K.; Hale, I.; Powell, W.; Hendre, P.; Jamnadass, Ramni H. (Elsevier, 2022)
A ‘systems approach’ to plant breeding is increasingly recognised as required to address broad global challenges including the transgression of multiple planetary boundaries. In this opinion piece we describe a systems approach to plant breeding that is based on advancing novel and creative linkages between existing breeding methods that are oriented to multiple global trends and values. We illustrate our concept for how biodiversity can be mobilised strategically to address pressing global needs by considering the case study of tree genetic improvement. We choose ‘tree diversity breeding’ as our example based on the increasingly crucial roles of trees in supporting continued human development and the environment, and because of trees’ enormous diversity that provides significant opportunities for a systems approach to genetic improvement.